Science Learning in Solar System Material with Differentiated Learning Styles Using the Project-Based Learning (PjBL) Model to Improve Cognitive Learning Outcomes - Puspananda Damayanti; Andista Candra Yusro; Tutik Wahyuni (Universitas Lambung Mangkurat, 2023)
This study aims to describe the observation of improving cognitive learning outcomes with learning style differentiation learning with the use of the Project Based Learning (PjBL) model. The study was carried out at a junior high school in Jombang district. The population based on the object of observation was carried out, namely class VII F and VII D students for the 2022/2023 school year, with a total population in this study of 62 people. Class VII D served as the control group for the study, and Class VII F served as the experimental group. The research sample was taken using the total sampling technique. Data was collected using tests with instruments like pretest and posttest question sheets. The average value of N-gain shows that the study's findings—namely, the improvement in learning outcomes of diversified learning styles utilizing the Project Based Learning (PjBL) model—have improved. The study's findings revealed that the average n-gain value in the experimental class was 0.74 in the high category and 0.69 in the medium category for the control class.These findings suggest that differentiated learning with the use of the PjBL model approach increases student learning outcomes more than conventional learning.